Parkinsonism following Bee Sting: A Case Report. (9th October 2012) - Mittal, Ruchika; Munjal, Sanjay; Khurana, Dheeraj; Gupta, Ashok
Abstract : We are reporting here a rare case of Parkinsonism (Hypokinetic dysarthria) caused after a bee stung, a member of the hymenoptera order. The main aim of this report is to orient the clinicians with the possibility of extrapyramidal syndromes because of hymenoptera stings.